Managing mobile devices with Configuration Manager System Center Current Branch - Daalmans, Peter; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"With the advent of containerization and ease of cloud availability, developers are required to explore new tools and frameworks in order to best utilize these technologies. Spring Framework's core features can be used by any Java application, but there are extensions to build web applications on top of the Java EE platform. In this video course, you'll start by learning how to configure Intune support and enable different platforms. Then you'll see how to manage your different device settings as well as different profiles such as WIFI, VPN ... After that, you'll explore compliance, conditional access, and mobile application management using Microsoft SCCM Current Branch. Next, you'll work with different mobile devices using Mobile Device Management in SCCM. Finally, you'll see how to troubleshoot MDM using client-side log files and SCCM's log files."--Resource description page.
Title from resource description page (Safari, viewed October 25, 2017).
Presenter, Peter Daalmans.
Keywords: Microsoft System center; Computer networks -- Management; Client/server computing; Electronic books